Understanding the Molecular Basis of Tyrosine Kinase Intrinsic Promiscuity Toward Binding Type-I and Type-II Kinase Inhibitors. KIT versus INSR as a Case Study - Shallal, Hassan M.; Russu, Wade A. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The PDGFR kinase subfamily exhibits a significantly more promiscuous capacity of binding to tested kinase inhibitors, both type-I and type-II, compared to INSR subfamily. Time dependent ensembles of both KIT and INSR apoenzymes, representing PDGFR and INSR subfamilies respectively, were generated using molecular dynamics (MD) experiments in order to seek explanations of the different overall binding attitudes of KIT and INSR. Topologically speaking, DFG-hinge distance tends to be shorter in INSR compared to KIT whereas the DFG-αC-helix distance fluctuates more significantly in INSR than in KIT. In terms of energetics, the binding area tends to be energetically more self-stabilizing in INSR relative to KIT. These results suggest that the binding area in INSR is different from that of KIT in topological, energetic, and dynamic terms with different overall tendency to bind to kinase inhibitors. The relevance of the assumptions, suggested by this study, to kinase drug discovery is also discussed.